Pemikiran Imam Al-Ghazali dalam Hukum Ekonomi Syariah - Mahendra, Roy Mahendra; Nasution, Ismail Fahmi Arrauf (Universitas Islam Negeri Raden Intan Lampung, 2023)
Al-Ghazali is one of the greatest economic thinkers in Islam. Using the monumental works of Ihya Ulumuddin, al-Mustashfa Mizan, al-Amal and At-Tibr al-Masbuk fi al-Nasihah al-MulukAl-Ghazal, he examines in detail the important aspects of Islamic economics. Because, according to him, economic development is part of the social obligations assigned by God. In his works, Al-Ghazali emphasizes justice, peace and stability as the basis for economic availability in the fields of production, consumption and distribution. For this reason, the role of the state in protecting it is very important. Keywords: Al-Ghazali, Economics, Islam